A multi-factor analysis approach for recycled asphalt mixture stockpile center location. (September 2020) - Han, Chengjia; Ma, Tao; Xu, Guangji; Chen, Siyu
Highlights: A multi-factor analysis approach for the optimum locations of RAP storage stations. GIS and Floyd algorithm were combined to find the most benefit solution. The cost-benefit analysis was applied to evaluated the warehouse location. The data of Jiangsu province expressway in China were used for verification. Abstract: The mixture recycling of reclaimed asphalt pavement (RAP) has become a widely used strategy in road maintenance. The article aimed at acquiring the optimum solutions to quantity and location distribution of RAP stockpile logistic centers over a regional highway network using a multi-factor analysis approach to further promote the development of asphalt recycling technology. Firstly, the economic radius of RAP stockpile logistic centers was calculated to determine the optimal number of RAP stockpile logistic centers according to the density of road network in the target region. Then, the proper location of each RAP stockpile logistic center was investigated employing ArcGIS buffer analysis and Floyd algorithm, with three factors taken into consideration (environment impacts, RAP material yield and consumption of each road in highway network, and the economic transport distance). Finally, upon the selection of each RAP stockpile logistic center site, the economic benefits were evaluated through cost-benefit analysis (CBA). In a case study based on the data of Jiangsu province expressway network, it suggested that an establishment of 13 RAP stockpile logistic centers will meet the recycling maintenance need of asphalt pavement over the whole highway network in Jiangsu province, contributing to a 6-year net maintenance benefit of about 70 million CNY.